Polyethylene glycol 20 kDa-induced vacuolation does not impair phagocytic function of human monocyte-derived macrophages - Schoenbrunn, Anne; Juelke, Kerstin; Reipert, Birgit M.; Horling, Frank; Turecek, Peter L. (Frontiers in Immunology, 2022)
Conjugation to polyethylene glycol (PEG) is commonly used to enhance drug delivery and efficacy by extending the half-life of the drug molecule. This has important implications for reducing treatment burden in diseases that require chronic prophylaxis, such as hemophilia. Clearance of PEG molecules with high molecular weights (≥ 40 kDa) has been reported to cause cellular vacuolation in mammals. Rurioctocog alfa pegol (PEGylated recombinant coagulation factor VIII) contains a 20-kDa PEG. This study investigated the effects of exposure to 20-kDa PEG (10 μg/ml to 10 mg/ml) on the morphology and function of human monocyte-derived macrophages (MDMs) in vitro. Exposure to PEG for 24 hours was associated with significant vacuolation only at concentrations of 1 mg/ml or more, which far exceed the levels associated with clinically relevant doses of rurioctocog alfa pegol. Immunofluorescence staining of PEG was detected in the cytoplasm of MDMs, indicating uptake into the cells. No impairment of MDM phagocytic activity (ability to ingest fluorescently labeled Escherichia coli) was observed with 24-hour exposure to PEG, even at concentrations associated with significant vacuolation. Furthermore, PEG exposure did not have significant effects on cytokine secretion in resting or lipopolysaccharide-stimulated MDMs, or on the expression of cell surface markers in stimulated MDMs. Cell viability was not affected by 24-hour exposure to PEG. In conclusion, vacuolation of human MDMs after exposure to 20-kDa PEG only occurred with PEG concentrations far in excess of those equivalent to clinically relevant doses of rurioctocog alfa pegol and did not affect MDM viability or functionality. Together, these results support the concept that PEG-mediated vacuolation is an adaptive cellular response rather than a toxic effect.